Analysis Of Willingness To Pay Of Broiler Chicken Consumers In Ranomeeto District - Muhammad Rival Feriawan; Bahari; Yusna Indarsyih (International Journal of Technology and Education Research, 2026)
This study aims to analyze consumers’ willingness to pay (WTP) for broiler chicken and the factors influencing it in Ranomeeto Market, South Konawe Regency. The research was conducted from January to August 2025, involving 100 respondents selected using accidental sampling. Data were collected through interviews and documentation, and analyzed using multiple linear regression. The results showed that 73% of consumers were willing to pay more for broiler chicken, with an average WTP value of IDR 38,677 per kilogram. The analysis revealed that income positively and significantly affects WTP, while the number of family members has a negative and significant effect. In contrast, age and education level did not significantly influence consumers’ WTP. The findings suggest that pricing strategies for broiler chicken should consider consumer purchasing power, with prices set slightly below the average WTP to maintain demand. Moreover, government supervision is needed to stabilize food prices and align them with consumers’ economic capacity.